Innovation for universal voice command - Amran, Atiela; Rahim, Nurin Sofea; Mohd Zaini, Nazatul Najwa; Amran, Nur Bilqis Dayini; Saliman, Nur Hizzati; Abdul Basir, Farah Safiyah (Academica Press Solutions, 2025)
The development of a universal voice command device involves problem identification, focusing on hands-free operation, voice assistance, and accessibility for elderly or disabled users. Key stages include ideation and market research, emphasizing user needs, ergonomic design, and competitor analysis. Research and design utilize a user-centered approach, integrating features like voice recognition, LED indicators, and tactile buttons for inclusivity. Engineering and development involve assembling hardware components (microphones, speakers) and implementing software for voice algorithms and connectivity (Wi-Fi, Bluetooth). Accessibility features like manual buttons, volume controls, and light cues are added for versatility. Manufacturing ensures durability and eco-friendliness while scaling production with quality control. Marketing and deployment target users with clear instructions and accessibility highlights. Feedback and iteration enable updates and feature enhancements to maintain relevance and effectiveness.